Analysis of serum bone turnover markers in female cynomolgus monkeys of different ages - Li, Ying; Cai, Qijun; Dong, Chenchen; Hou, Lu; Li, Yingxin; Guo, Bin; Zeng, Chunyuan; Cheng, Yong; Shang, Jingjie; Ling, Xueying; Gong, Jian; Xu, Hao (Frontiers in Endocrinology, 2022)
Abstract Objective: The purpose of this study was to examine bone turnover markers, estradiol, parathyroid hormone, and 25 hydroxyvitamin D, in cynomolgus monkeys at different ages to improve our understanding of the changes in bone turnover markers throughout the life cycle of cynomolgus monkeys and to provide a basis for the establishment of a non-human primate model of osteoporosis. Methods: Total Body Bone Mineral Density and Total Body Bone Mineral Content were measured using Dual-Energy X-Ray Absorptiometry in cynomolgus monkeys at different ages. Serum bone conversion marker levels were measured using enzyme immunoassays at each age group, and the relationship between bone turnover markers and age was assessed by Spearman rank correlation analysis to investigate the relationship between bone turnover markers and age in female cynomolgus monkeys. Results: Total Body Bone Mineral Density in female cynomolgus monkeys peaked at 10 years of age and then formed a plateau that was maintained until old age. Procollagen I Aminoterminal Propeptide, Bone Alkaline Phosphatase, Osteocalcin, and C-Terminal Telopeptide Of Type I Collagen peaked at 1 to 3 years of age and gradually decreased with age, leveling off by 10 years of age. Estradiol, parathyroid hormone, and 25 hydroxyvitamin D, follicle-stimulating hormone, luteinizing hormone, were not significantly different among age groups. Conclusion: This paper provides data on trends in bone turnover markers throughout the life cycle of female cynomolgus monkeys, which are similar to human changes.